Sorojenci pri porodu - Dolinar, Polona (Obzornik zdravstvene nege, 2012)
Introduction: Within the context of natural childbirth, homely environment is encouraged. This includes also the presence of family members. It started by promoting the father's attendance and involvement in the birth of his child. Besides the integration of the child's father and adult significant others at the birth experience, it is worth considering also the involvement of older siblings. The purpose of this article is to test the hypotheses that the presence of siblings has positive effects on children and that it positively affects mothers. The aim of the study was also to gather data about the necessary pre-conditions for the presence of siblings at birth. Methods: The study was based on a descriptive research method. A review of the literature (1974 - 2006) and the analysis of the scientific studies of the relevant issuewere conducted. Results: Not many studies on the effects of siblings at birth have hitherto been performed. Most of the foreign studies date back morethan twenty years ago. The findings of the present research indicate that the presence of siblings at birth has a positive impact on all family members on condition that it is the siblings' independent decision and they are provided good preparation and support before and during this experience. Discussion and conclusion: In Slovenia, birthing women are currently not yet granted the option of having older children present at birth. Before any recommendations to change the current practice are given, additional longitudinal research is necessary to provide more clear-cut answers as to thebenefits and possible negative effects of siblings at birth. A final and equally important point is that, the midwives should be also adequately prepared for such an experience.
Keywords: analysis of quantitatve studies; birth preparation; childbirth; delivery; home birth; porod; porod na domu; priprava; siblings; siblings relationship; sorojenci